Development of an Endurance Test Procedure for Vehicle Control Arm through Vehicle Dynamic Testing and Load Transfer Analysis - Nuurshafiqah Anuar; Syabillah Sulaiman; Muhamad Asri Azizul; Shaiful Fadzil Zainal Abidin; Norirda Mohamed; Rahmah Mahmudin; Norhasikin Ismail (Automotive Experiences, 2024)
This research studies the forces applied to various vehicle control arms through different static and dynamic conditions during acceleration and braking condition. This study is targeting the important role that control arms play in ensuring stability and dynamics of vehicles, particularly when electric powertrains are added to chassis platforms created for conventional internal combustion engine (ICE). The study was designed with three phases: Fundamental of control arm dynamics (Phase 1), math formulations into theoretical models (Phase 2) and then experimental validation using the real rail component measurements (Phase 3). Tests were carried out on a straight track at a speed of 15 km/h and 30 km/h targeting the rear axle in an accelerating and the front axle in a braking condition. Results indicated that at 15 km/h, the acceleration of the rear axle was between 0.63 g and 0.49 g whereas at 30 km/h it was between 0.68 g and 0.70 g. During braking at 15 km/h, the front axle's acceleration ranged from a minimum of 0.62 g to a maximum of 0.70 g. At 30 km/h, the acceleration ranged from a minimum of 0.73 g to a maximum of 0.81 g. This suggests that there is a marked disparity in the dynamic action or response of sprung mass and unsprung mass at the different loading conditions. It emphasizes the need for additional support in the control arms and better control over the forces when the electric powertrains will be introduced. All of these have laid a basis for further research aimed at improving the designs of the vehicle structures in advance for the emerging powertrain technologies.